Generative AI Readiness of EFL Lecturers in Buleleng District: An Explanatory Sequential Study - Kori, Ni Made Dwi Apsari; Santosa, Made Hery; Paramartha , A.A. Gede Yudha (JET ADI BUANA, 2026)
Readiness in using Generative Artificial Intelligence (GenAI) is crucial for lecturers to ensure meaningful and ethical integration of AI in higher education. It encompasses not only technical competence and the ability to interact with students using AI but also ethical awareness, which is essential to prevent plagiarism, bias, and misuse of AI tools. Understanding lecturers’ readiness, particularly in the ethical dimension, is therefore important. This study examined the readiness of EFL lecturers teaching at 3 universities in the Buleleng District of Bali. An explanatory sequential mixed-method design was employed, combining a questionnaire adapted from the Readiness for Artificial Intelligence Scale (RAIS) with semi-structured interviews. From a total population of 62 EFL lecturers with prior experience using GenAI, 28 participated in the survey, and 5 were involved in the interview phase. Results indicate that lecturers are ready to use GenAI, and lecturers have high ethical awareness of AI integration. However, lecturers feel less ready to implement ethical practices of GenAI. Qualitative findings reveal that lecturers’ readiness is influenced by experience, repeated use of GenAI, and positive perceptions of its usefulness. Meanwhile, lower ethical readiness is associated with hesitation, confusion about ethical boundaries, and unclear institutional or national AI regulations. Although a recent national Joint Regulation on AI in Indonesia (SKB) has been introduced, its implementation depends on individual educational institutions, as the regulation delegates its operationalization to them.